KORELASI MOTIVASI BERPRESTASI DENGAN KINERJA DOSEN IAIN AR-RANIRY BANDA ACEH - Intan Afriati (Islam Futura, 2012)
Every lecturer should have a good performance to improve student achievement. One of the factors to improve the lecturers’ performance is achievement motivation. This research was conducted to figure out a positive and significant relationship between achievement motivation with lecturer’s performance. The study was conducted through quantitative approach. The data was collected through questionnaires which were given to 77 respondents of 343 lecturers at IAIN Ar-raniry Banda Aceh. The analysis of the data is Pearson product moment correlation analysis. The results showed that the correlation coefficient (r) is 0.574. The correlation number indicates that both characteristic and the strength of the relationship is “medium”. It indicates that the the closeness of the relationship between achievement motivation and lecturer’s performance of IAIN Ar-Raniry is at “medium” level. The number of tcount is 6.077 while the number of ttable = 1,992 at the confidence level 95% sig. 5% 2-tailed and dk = n – 1 = 76. Thus, tcount is 6.077 > ttable is 1.992 show that there is a significant relationship between achievement motivation and performance of IAIN Ar-Raniry lecturer. It means that if the achievement motivation is increased, the motivation performance of IAIN Ar-Raniry lecturer will be increased.